Organic materials for quantum computation - Rival, O (2009)
Quantum mechanics has a long history of helping computer science. For a long time, it provided help only at the hardware level by giving a better understanding of the properties of matter and thus allowing the design of ever smaller and ever more efficient components. For the last few decades, much research has been dedicated to finding whether one can change computer science even more radically by using the principles of quantum mechanics at both the hardware and algorithm levels. This field of research called Quantum Information Processing (QIP) has rapidly seen interesting theoretical developments: it was in particular shown that using superposition of states leads to computers that could outperform classical ones. The experimental side of QIP however lags far behind as it requires an unprecedented amount of control and understanding of quantum systems. Much effort is spent on finding which particular systems would provide the best physical implementation of QIP concepts. Because of their nearly endless versatility and the high degree of control over their synthesis, organic materials deserve to be assessed as a possible route to quantum computers. This thesis studies the QIP potential of spin degrees of freedom in several such organic compounds. Firstly, a study on low-spin antiferromagnetic rings is presented. It is shown that in this class of molecular nanomagnets the relaxation times are much longer than previously expected and are in particular long enough for up to a few hundred quantum operations to be performed. A detailed study of the relaxation mechanisms is presented and, with it, routes to increasing the phase coherence time further by choosing the suitable temperature, isotopic and chemical substitution or solvent. A study of higher-spin systems is also presented and it is shown that the relaxation mechanisms are essentially the same as in low-spin compounds. The route to multi-qubit system is also investigated: the magnetic properties of several supermolecular assemblies, in particular dimers, are investigated. Coupling between neighbouring nanomagnets is demonstrated and experimental issues are raised concerning the study of the coherent dynamics of dimers. Finally a study of the purely organic compound phenanthrene is reported. In this molecule the magnetic moment does not result from the interactions between several transition metal ions as in molecular nanomagnets but from the photoexcitation of an otherwise diamagnetic molecule. The interest of such a system in terms of QIP is presented and relaxation times and coupling to relevant nuclei are identified.